JOB SATISFACTION AND TURNOVER INTENTION AT PT. X YOGYAKARTA - Rembang, Marsella Alfreyni; Wijono, Sutarto (International Journal Labs, 2023)
This quantitative study investigates the correlation between job satisfaction and turnover intention among employees at PT. X Yogyakarta. Utilizing a correlational design, the researchers sampled 48 participants aged between 21 to 48 years old, employing a saturated sampling technique. The research employed the Turnover Intention scale and the Job Satisfaction scale for measurement. The findings affirm a significant and negative relationship between job satisfaction and turnover intention among PT. X Yogyakarta's workforce. In other words, higher job satisfaction levels correspond to lower turnover intention, while lower job satisfaction leads to higher turnover intention. These results have crucial implications for the organization, emphasizing the importance of enhancing job satisfaction to mitigate turnover intentions. By understanding the inverse relationship between these two variables, PT. X Yogyakarta can devise targeted strategies and interventions to improve overall employee satisfaction, consequently reducing turnover rates. It is worth noting that the study's correlational design does not imply causation, and further research might explore the underlying factors that contribute to job satisfaction and turnover intention at PT. X Yogyakarta. Nevertheless, these findings offer valuable insights for the organization to foster a positive work environment, boost employee morale, and retain a committed and satisfied workforce.